Education and Income Inequality in the Regions of the European Union - Andres Rodriguez-Pose; Vasileios Tselios (European Regional Science Association (ERSA), 2006)
The paper provides an empirical study of the determinants of income inequality across regions of the EU. Using the European Community Household Panel data set for 102 regions over the period 1995-2000, it analyses how microeconomic changes in human capital distribution affect income inequality. Human capital distribution is measured in terms of both human capital stock, as well as human capital inequality. Income and human capital inequalities are calculated by a generalised entropy index (Theil index). Different static and dynamic panel data analyses are conducted in order to reduce measurement error on inequalities and minimise potential problems of omitted-variable bias. The regression results suggest that, in the short term, human capital inequality is negatively associated to the average regional income and the average level of education of the population. The results also highlight that a highly unequal distribution of education level completed is associated to lower, rather than to higher inequality, highlighting the effectiveness of the European social system or, from a different perspective, the lack of responsiveness of EU labour market to differences in qualifications and skills. Additionally, high unemployment is associated with higher income inequality, while urbanisation has the opposite effect.
Keywords: 330